Comentarios a la sentencia del Tribunal Constitucional peruano que prohíbe la distribución de la denominada Anticoncepción Oral de Emergencia - Tejada Pinto, Paolo (Revista de Derecho, 2020)
Through ruling dating October 16th, 2009 which resolved the injunction interposed by a NGO the Peruvian Constitutional Tribunal prohibited the Ministry of Health from distributing the day after pill also known as Emergency Oral Contraception (EOC) for free. Claiming the pertinence of principles which are applicable in constitutional protection and which are based on the existence of reasonable doubt regarding the effects of the EOC, a majority of Magistrates pointed out that the distribution of this drug could be abortive and therefore its free distribution is unconstitutional. Naturally the Ruling has been subject to many commentaries, both favourable as well as not favourable. The present article analyzed the controversial issues and the way in which they were approached by the Tribunal.
Keywords: emergency oral contraception; day after pill; abortion; right to life